Pemberdayaan Masyarakat Pada Usaha Mikro Kecil Menengah Anugerah Foods Sentra Aneka Keripik di Desa Jungke Magetan - Dian Citaningtyas Ari Kadi; Rizal Ula Ananta Fauzi (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
Community service programs are programs that aim to help the community without expecting anything in return. This service program seeks to help the Micro, Small, and Medium Enterprises (MSME) group